Examination of stable carbon and oxygen isotopic variability in the cellulose and wholewood of Castanea sativa Mill., Fagus sylvatica L., Pinus sylvestris L. and Quercus robur L. - Sladden, B. (Acta silvae et ligni, 2018)
This paper presents results from a comparison of wholewood and cellulose carbon and oxygen isotope ratios for four UK tree species. These species occur within the historic buildings archive as both primary and supplementary construction materials and have been used to reconstruct the climate of the past. New advances in the application of stable isotopes have widened the scope of the isotope approach, but require the time-consuming purification of cellulose. Comparison of the oxygen and carbon isotope signals preserved in the wood and cellulose components confirms and builds upon previous research in this field and provides additional insight into the covariance of these two sample types between species, an
Keywords: dendrochronology; dendroclimatology; dendroklimatologija; dendrokronologija; drevesne branike; stabilni izotopi; stable isotopes; tree ring; Velika Britanija